The impact of verbal bullying on self-confidence in fourth grade elementary school students - Mia Sari; Yulianti; Romia Hari Susanti; Suci Indah Susanti; Ngulmi Khamidah; Fariz Ardi Kusuma; Laura Adhi Pramadhika Branigan (Universitas Kanjuruhan Malang, 2026)
This research is motivated by the prevalence of bullying behavior at the elementary school level that affects students’ self-confidence in learning. The purpose of this study is to identify the impact of verbal bullying on students' self-confidence in learning. A qualitative case study was conducted at SD Negeri 2 Pagedangan, Malang Regency, involving 20 fourth-grade students, classroom teachers, student affairs teachers, and parents. Data were collected through observation, in-depth interviews, questionnaires, and documentation. The results indicate that dominant forms of verbal bullying include teasing, giving nicknames, shouting, threatening, and humiliating. These behaviors negatively affect self-confidence indicators such as self-confidence, optimism, objectivity in thinking, responsibility, and rationality in acting. Victims tend to withdraw, become passive in learning, and fear participation. The findings highlight the need for preventive measures and proper handling of verbal bullying to maintain elementary students’ self-confidence.